2016
DOI: 10.1021/acs.inorgchem.5b02287
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency cw-EPR and DFT Studies of an Apparent Compressed Octahedral Cu(II) Complex

Abstract: The syntheses and single-crystal X-ray structures of the mononuclear complexes [Cu(bmet)](ClO4)2·H2O, [Cu(bmet)]Br2·2MeCN, and [Zn(bmet)](ClO4)2·H2O (bmet = N,N'-bis(2,2'-bipyridin-6-ylmethyl)ethane-1,2-diamine) are described. All three complexes feature a central metal ion bound to all six N atoms of the bmet ligand, which displays a meridional-facial-facial-meridional (mffm) configuration. The three complexes show one N-M-N axis to be significantly shorter than the others in agreement with an apparent compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
(64 reference statements)
2
8
0
Order By: Relevance
“…The X‐band EPR spectra of polycrystalline powders of compounds 1 – 4 were recorded at room temperature (298 K) (Figure S2). The values of EPR parameter g are consistent with a distorted octahedral arrangement (CuN 2 O 4 ) for compound 1 and distorted square pyramidal arrangement (CuN 2 O 2 O′) for compounds 2 – 4 which indicate the dx2y2 ground state of Cu(II) ion as listed in Table …”
Section: Resultssupporting
confidence: 68%
“…The X‐band EPR spectra of polycrystalline powders of compounds 1 – 4 were recorded at room temperature (298 K) (Figure S2). The values of EPR parameter g are consistent with a distorted octahedral arrangement (CuN 2 O 4 ) for compound 1 and distorted square pyramidal arrangement (CuN 2 O 2 O′) for compounds 2 – 4 which indicate the dx2y2 ground state of Cu(II) ion as listed in Table …”
Section: Resultssupporting
confidence: 68%
“…The mean Cu-N bond length is 2.116 Å , which is similar to that of reported copper(II) complexes (Bhat et al, 2011(Bhat et al, , 2017. Four long bonds [Cu-N2 = Cu-N2 i = 2.189 (3) Å and Cu-Cl1 = Cu-Cl1 i = 2.5579 (14) Å ; symmetry code: (i) Àx + 1, y, Àz + 3 2 ] are in a plane and two short bonds [Cu-N1 = Cu-N1 i = 2.043 (2) Å ] are trans to each other, suggesting a compressed octahedral geometry; similar compressed octahedral geometries have been observed for some octahedral copper complexes (Hall et al, 2016;Solanki et al, 1998;Biswas et al, 2008). The heterocyclic ligands in the title complex are oriented perpendicular to each other, which may be due to the steric clash of H atoms of the organic rings, which is similar to the situation seen in a five-coordinated [CuCl(1,10-phenantroline) 2 ]Cl complex (Onawumi et al, 2010).…”
Section: Crystal Structurementioning
confidence: 59%
“…Furthermore, after the reaction was completed, we observed a green copper precipitate, which was the same as that formed from the control reaction of 1a with Cu 2 O and 1,10-phen at 120 °C for 3.0 h in CB. The electron paramagnetic resonance (EPR) experiment of the green solid in DMSO suggested that a Cu­(II) species existed . The X-ray diffraction experiment further confirmed that the single crystal 4 grown from the green copper solid was a complex of 1,10-phen and CuCl 2 (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%